Monosynaptic Projections to Excitatory and Inhibitory preBötzinger Complex Neurons - Yang, Cindy F.; Kim, Euiseok J.; Callaway, Edward M.; Feldman, Jack L. (Frontiers in Neuroanatomy, 2020)
The key driver of breathing rhythm is the preBötzinger Complex (preBötC) whose activity is modulated by various functional inputs, e.g., volitional, physiological, and emotional. While the preBötC is highly interconnected with other regions of the breathing central pattern generator (bCPG) in the brainstem, there is no data about the direct projections to either excitatory and inhibitory preBötC subpopulations from other elements of the bCPG or from suprapontine regions. Using modified rabies tracing, we identified neurons throughout the brain that send monosynaptic projections to identified excitatory and inhibitory preBötC neurons in mice. Within the brainstem, neurons from sites in the bCPG, including the contralateral preBötC, Bötzinger Complex, the nucleus of the solitary tract (NTS), parafacial region (pFL/pFV), and parabrachial nuclei (PB), send direct projections to both excitatory and inhibitory preBötC neurons. Suprapontine inputs to the excitatory and inhibitory preBötC neurons include the superior colliculus, red nucleus, amygdala, hypothalamus, and cortex; these projections represent potential direct pathways for volitional, emotional, and physiological control of breathing.